The Structure of Students' Metacognition in Problem Solving of Two Physics Contexts - Khairunnisa H Jusuf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to describe students' metacognition in problem solving of two physics contexts, i.e. static fluid and heat. The subjects of the research were twenty-five second grade students of a high school in Palu. From the subjects, six students were selected as respondents using selection test. The six respondents represented three categories, i.e., high, medium, and low ability. The data of this research, collection using essay test of physics problems in the two contexts, problem solving activities in setting of thinking-aloud, and it was followed by interview. Based on data analysis it was found that, students of the high category do aspects from three components of metacognition, i.e. awareness, evaluation dan regulation. Students of the medium category do aspects from components of metacognition awareness, but occasionally do aspects from components of metacognition evaluation for considered difficult problems. Students of the low category only do aspects from components of metacognition evaluation by being aware for their own limitations in problem solving. Evaluation is the components of metacognition that always be there for all students' categories, and this applies in two contexts of physics materials. The ability of understand learning influences problem solving which is closely related to metacognition behaviour.